LEMAK TENGKAWANG SEBAGAI BAHAN DASAR LIPSTIK - R. Esa Pangersa Gusti; Totok K. Waluyo (Jurnal Penelitian Hasil Hutan, 2016)
Cocoa butter has long been used as a base ingredient for lipstick. Illipe nut's fat is known to have similar characteristics to those of cocoa butter, thus expectedly, it could be used as an alternative substitute for cocoa butter in lipstik manufacturing. This paper studies the appropriate Illipe nut's fat formulation for lipstick manufacturing. Water-based (WB1, WB2, WB3, WB4) and oil-based (M1, M2, M3, M4, M5) formulations with illipe nut fat content of 2, 3, 4 and 5% were tested. The illipe nut's fat was produced from Shorea pinanga collected from West Java. Physical properties (i.e hardness and melting point) and organoleptic test (texture, shine, polish ability, odor and color) were analyzed. The results showed that M3 formulation with 2% illipe nut's fat level had similar physical properties to those of commercial lipsticks. Furthermore, the organoleptic test revealed that M5 formulation with 3% fat level was the most preferred by respondents. To obtain lipsticks performance which meets the requirements in commercial lipsticks criteria and also satisfies the respondent's preference, a combination of M3 and M5 formulation is recommended.